2007
DOI: 10.1016/j.neulet.2006.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent loss of NGF signaling in the rat basal forebrain is due to disrupted MAPK activation

Abstract: The loss of Nerve Growth Factor (NGF) and its high affinity receptor TrkA has been implicated in the loss of cholinergic tone and function in Alzheimer's disease (AD) and normal aging. We employed an animal model of aging, the aged rat, which also exhibits memory loss and NGF alterations. Basal forebrain TrkA levels increased after injection of NGF in the hippocampus within one-hour in young rats, but this response was diminished in aged animals as determined by Western blot analysis. Further, NGF activated MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 43 publications
(49 reference statements)
2
35
0
Order By: Relevance
“…However, these two different pathways involve mutual crosstalk [26], which can also be confirmed by the findings of the present study. In this study, the p-Erk/t-Erk ratios and CREB levels in the soleus of diabetic rats were not affected by treadmill exercise.…”
Section: Discussionsupporting
confidence: 91%
“…However, these two different pathways involve mutual crosstalk [26], which can also be confirmed by the findings of the present study. In this study, the p-Erk/t-Erk ratios and CREB levels in the soleus of diabetic rats were not affected by treadmill exercise.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies on PS1 expression in the developing brain and the impaired neuronal development in PS1 null mice suggested that factors involved in neuronal differentiation and survival influence the PS1 protein level (Ribaut-Barassin et al 2003;Saura et al 2004). Some of these factors (TGF-b, NGF, BDNF) are neurotrophic in nature and show age dependent expression (Silhot et al 2005;Williams et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…16,17) Figure 3A shows that Re and Rd could activate ERK and Akt with phosphorylation as much as NGF, suggesting that Re and Rd are closely related with the NGF-TrkA signaling pathway (Fig. 3B).…”
Section: Effect Of Ginsenosides On the Cholinergic Markers In N2a Cellsmentioning
confidence: 95%